The relationship between the hardness of potable water and cardiovascular and ischaemic heart disease mortality in South African urban areas - Derry, Christopher William (Department of Public Health and Family Medicine, 2017)
Studies carried out in a number of countries have revealed statistically significant negative correlations between death rates from cardiovascular disease (CVD) or ischaemic heart disease (IHD), and the hardness of local water supplies, a phenomenon which is known as the "water story". These findings have not, however, been universal and it was decided that a study carried out in South Africa with its high CVD and IHD death rates, might yield meaningful results to contradict or support existing findings. In 1983 a pilot study was thus initiated using a spatial model and a more detailed study began in 1984. This study ultimately involved the correlation of standardized mortality ratios (SMRs) for CVD and IHD with total water hardness and with a number of contributory and associated water quality factors. The study supported the hypothesised "water story", showing the existence of negative correlations between standardized mortality ratios (SMRs) for both CVD and IHD, and the hardness of potable water, whether measured as total hardness or as its two major contributory cations, calcium and magnesium. The level of statistical significance at which this correlation occurred, however, varied with differences in methodological approach. A "population-unweighted" methodology, which was applied to enable comparison with a number of previously published studies, pointed to potassium (a known hypertension normalisor) in permanently hard water as being an important factor. Problems inherent to each methodological approach have been discussed as has the need for improved data. In this regard, the need for a National water quality data bank has been emphasised.